Codon misreading tRNAs promote tumor growth in mice - Santos, Mafalda (RNA Biol, 2018)
Deregulation of tRNAs, aminoacyl-tRNA synthetases and tRNA modifying enzymes are common in cancer, raising the hypothesis that protein synthesis efficiency and accuracy (mistranslation) are compromised in tumors. We show here that human colon tumors and xenograft tumors produced in mice by two epithelial cancer cell lines mistranslate 2- to 4-fold more frequently than normal tissue. To clarify if protein mistranslation plays a role in tumor biology, we expressed mutant Ser-tRNAs that misincorporate Ser-at-Ala (frequent error) and Ser-at-Leu (infrequent error) in NIH3T3 cells and investigated how they responded to the proteome instability generated by the amino acid misincorporations. There was high tolerance to both misreading tRNAs, but the Ser-to-Ala misreading tRNA was a more potent inducer of cell transformation, stimulated angiogenesis and produced faster growing tumors in mice than the Ser-to-Leu misincorporating tRNA. Upregulation of the Akt pathway and the UPR were also observed. Most surprisingly, the relative expression of both misreading tRNAs increased during tumor growth, suggesting that protein mistranslation is advantageous in cancer contexts. These data highlight new features of protein synthesis deregulation in tumor biology.